Efficiencies of Horizontal and Vertical Baffle Mixers - Jude Iloabuchi Obianyo; J. C. Agunwamba (Ital Publication, 2019)
Efficiencies of sedimentation tanks with horizontal and vertical baffle mixers were studied, compared, and also to determine the optima values of factors of clarification in the sedimentation tanks. These are the discharge, basin baffle spacing and dosing factors, thereby comprises three factors at five levels for a 5k factorial design model. 2.0 mg/l of clay solution was introduced into the basin at discharge rates of 48.75 ml/s, 55.07 ml/s, 60.34 ml/s, 62.45 ml/s and 63.27 ml/s respectively. Alum solution was introduced as coagulant at the inlet of the basin, samples were collected both from the basin and the outlet and concentrations of flocs were measured. Plots of variation of total outlet and average outlet floc with dosing rates for horizontal and vertical mixers show that vertical mixers are better only at discharge of 48.75 ml/s, but horizontal mixers are better at 55.05 ml/s, 60.34 ml/s, 62.45 ml/s and 63.27 ml/s. Variation of grand total floc with dosing rates is also in favour of horizontal mixers. Plots of outlet floc against dosing rates at 48.75 ml/s discharge show that horizontal mixer spaced at 100 mm is better with maximum sediment/floc of 333 10-4 g at a dosing rate of 0.55 ml/s, at 55.07 ml/s discharge vertical mixer is better with 250 mm spacing giving maximum sediment of 985 10-4 g at a dosing rate of 0.95 ml/s. For 60.34 ml/s discharge, horizontal mixer is better at 250 mm spacing with maximum sediment of 307 10-4 g at 0.75 ml/s dosing rate. In the case of 62.45 ml/s discharge, horizontal mixer at a spacing of 300 mm is better with a maximum deposit of 335 10-4 g at a dosing rate of 0.95 ml/s, and for discharge of 63.27 ml/s, horizontal mixer is better at 150 mm spacing having a maximum sediment of 715 10-4 g for a dosing rate of 0.35 ml/s. Response surface methodology (RSM) presented by Montgomery, 2008 was further used for the analysis of data in this study for more reliable inference because it optimized the responses of these three variables. It was observed that for the vertically placed baffles, the stationary points of response surface for discharge rate, baffle spacing and dosing rate are 80.56762847 ml/s, 100.00000 mm and 0.04965779 ml/s, while for horizontally placed baffles, it was 70.636018 ml/s, 332.864704 mm and 1.402526 ml/s, however, these results indicate that horizontally placed baffle mixers are better than vertically placed baffle mixers.